2003
DOI: 10.1007/s11745-003-1183-9
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of plasmalogen markedly increased plasmalogen levels of blood plasma in rats

Abstract: Plasmalogens, a subclass of phospholipids, are widely distributed in human and animals, and are taken into the body as food. However, no data exist on the intestinal absorption or fate of ingested plasmalogen. Here, we determined whether dietary plasmalogen is absorbed and whether blood and tissue concentrations increased in normal male Wistar rats by using four separate experiments. Phospholipids containing more than 20 wt% of plasmalogen extracted from the bovine brain were incorporated into test diets (10-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…Moreover, plasmalogens exert antioxidant capabilities via their vinyl-ether bond (Yavin et al, 2002), and neonates who have lower erythrocyte levels of plasmalogens than older children (Labadaridis et al, 2009) could be more vulnerable to oxidative stress. As, dietary plasmalogens are absorbed by the intestine and delivered intact to tissues (Nishimukai, Wakisaka, & Hara, 2003), their intake during early life might be essential, but optimal daily consumption is not known yet. However, based on an animal study, it was estimated that the SM consumption by breast-fed infants should be from 50 to 150 mg per day for promoting gut development (Motouri et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plasmalogens exert antioxidant capabilities via their vinyl-ether bond (Yavin et al, 2002), and neonates who have lower erythrocyte levels of plasmalogens than older children (Labadaridis et al, 2009) could be more vulnerable to oxidative stress. As, dietary plasmalogens are absorbed by the intestine and delivered intact to tissues (Nishimukai, Wakisaka, & Hara, 2003), their intake during early life might be essential, but optimal daily consumption is not known yet. However, based on an animal study, it was estimated that the SM consumption by breast-fed infants should be from 50 to 150 mg per day for promoting gut development (Motouri et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Vinyl ether double bonds in the plasmalogen are known to be sensitive to acid; however, Nishimura et al (34) demonstrated that dietary plasmalogen was absorbed from the intestine in rats. In the present study, the main lipid classes of the dietary phospholipid are PC and LysoPC, and the ratio of PE is low.…”
Section: Discussionmentioning
confidence: 99%
“…Among glycerophospholipids, plasmalogens have been noted as an antioxidant phospholipid in vitro and in vivo [1][2][3]. Moreover, uptake of plasmalogens was speculated to prevent the lipid oxidation of vascular epithelial cells, since it was absorbed into the intestinal tract followed by a large increase in the plasmalogen level in blood plasma [4]. However, a source of plasmalogen is not readily available.…”
Section: Introductionmentioning
confidence: 99%